Surface acting is related to emotional exhaustion among staff members working in high secure forensic psychiatric care. Issue 3 (4th May 2022) - de Vries, Meike G.; Verkes, Robbert-Jan; Bulten, Berend H.
ABSTRACT: The concept of 'emotional labour' has been suggested as a useful framework for studying the relationship between emotionally demanding work and well being of health-care staff. The framework distinguishes 'surface acting' from 'deep acting' and suggests a predominant reliance on surface acting as a risk for emotional exhaustion. The relationship between emotional demands and emotional exhaustion among staff members working in high secure forensic psychiatric care (n = 131) was studied using the framework of emotional labour. Surface acting was found to partly mediate the relationship between emotional demands and emotional exhaustion. Experiencing the relationship with the manager as supportive contributed negatively to the prediction of emotional exhaustion. Workplace support did not moderate the relationship between emotional labour and emotional exhaustion. Although staff members working on wards in the direct care of forensic psychiatric patients tend to use both deep and surface acting during their work, our study results also show that deep acting and surface acting are differently related to emotional exhaustion. The framework of emotional labour indeed showed to be a useful paradigm within this population. Therefore, suggestions are made to pay attention to emotional labour strategies in future research and practice.